Gender Biases in Estimation of Others’ Pain - Zhang, Lanlan; Losin, Elizabeth A. Reynolds; Ashar, Yoni K.; Koban, Leonie; Wager, Tor D. (The journal of pain, 2021)
•In two studies, perceivers under-estimated female patients’ pain compared with males’ pain.•Perceivers’ pain-related gender stereotypes predicted pain estimation biases.•Perceivers prescribed more psychotherapy for female and more pain medicine for male patients. Caregiving and other interpersonal interactions often require accurate perception of others’ pain from nonverbal cues, but perceivers may be subject to systematic biases based on gender, race, and other contextual factors. Such biases could contribute to systematic under-recognition and undertreatment of pain. In 2 experiments, we studied the impact of perceived patient sex on lay perceivers’ pain estimates and treatment recommendations. In Experiment 1 (N = 50), perceivers viewed facial video clips of female and male patients in chronic shoulder pain and estimated patients’ pain intensity. Multi-level linear modeling revealed that perceivers under-estimated female patients’ pain compared with male patients, after controlling for patients’ self-reported pain and pain facial expressiveness. Experiment 2 (N = 200) replicated these findings, and additionally found that 1) perceivers’ pain-related gender stereotypes, specifically beliefs about typical women's vs. men's willingness to express pain, predicted pain estimation biases; and 2) perceivers judged female patients as relatively more likely to benefit from psychotherapy, whereas male patients were judged to benefit more from pain medicine. In both experiments, the gender bias effect size was on average 2.45 points on a 0–100 pain scale. Gender biases in pain estimation may be an obstacle to effective pain care, and experimental approaches to characterizing biases, such as the one we tested here, could inform the development of interventions to reduce such biases. Perspective: This study identifies a bias towards underestimation of pain in female patients, which is related to gender stereotypes. The findings suggest caregivers’ or even clinicians’ pain stereotypes are a potential target for intervention.